2011
DOI: 10.1124/jpet.111.179622
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-Induced Internalization of CC Chemokine Receptor 5 as a Mechanism to Inhibit HIV Replication

Abstract: The chemokine G protein-coupled receptor CC chemokine receptor 5 (CCR5) is used as an entry gate by CCR5-tropic and dual-or CCR5/CXC chemokine receptor 4-tropic strains of HIV to enter the human host cells. Thus, CCR5 antagonists (i.e., maraviroc) have been proven to be clinically effective by preventing the interaction between viral glycoprotein 120 and CCR5 and thus impeding viral entry into host cells. However, the emergence of HIV strains resistant to CCR5 antagonists has been reported in vitro and in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
1
15
1
Order By: Relevance
“…We also showed that the chemokines tested in this study activated G proteins with potencies that generally match those detected for ␤-arrestin recruitment and other assays, but with subtle changes in the rank order according to assay. Thus, the behavior of chemokines contrast to the situation encountered in other studies with some synthetic small molecules that show agonism in one assay but antagonism in another (30,31). Collectively, our results suggest the existence of a moderate signaling bias between chemokines acting on the same receptor.…”
Section: Bias (␤) G␣contrasting
confidence: 65%
“…We also showed that the chemokines tested in this study activated G proteins with potencies that generally match those detected for ␤-arrestin recruitment and other assays, but with subtle changes in the rank order according to assay. Thus, the behavior of chemokines contrast to the situation encountered in other studies with some synthetic small molecules that show agonism in one assay but antagonism in another (30,31). Collectively, our results suggest the existence of a moderate signaling bias between chemokines acting on the same receptor.…”
Section: Bias (␤) G␣contrasting
confidence: 65%
“…Such a biased drug would cause receptor internalization, thereby preventing virus interaction with CCR5 and a lack of potential side effects after unwanted cellular signaling. Importantly, these properties were recently presented in ESN-196, a novel small-molecule CCR5-targeting ligand that induced CCR5 sequestration without promoting chemotaxis (47). Theoretically, targeting human components involved in the HIV infection cycle instead of the viral proteins would decrease the risk of resistance (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…The CCR5 response may also be biased with synthetic small molecules. For instance, YM-370749 and ESN-196 promote strong calcium mobilization and receptor internalization but not cell migration (20,21). However, the signaling pathways activated by synthetic small molecules at chemokine receptors remains often unknown.…”
mentioning
confidence: 99%